Duration of untreated eating disorder and relationship to outcomes: A systematic review of the literature. (23rd June 2020) - Austin, Amelia; Flynn, Michaela; Richards, Katie; Hodsoll, John; Duarte, Tiago Antunes; Robinson, Paul; Kelly, Jonathan; Schmidt, Ulrike
Abstract: Objective: This systematic review assesses the average duration of untreated eating disorder (DUED) in help‐seeking populations at the time of first eating disorder (ED) treatment and investigates the relationship between DUED and symptom severity/clinical outcomes. Method: PRISMA guidelines were followed throughout. Selected studies provided information on either: (i) length of DUED, (ii) components of DUED, (iii) cross‐sectional associations between DUED and symptom severity, (iv) associations between DUED and clinical outcomes, or (v) experimental manipulation of DUED. Study quality was assessed. Results: Fourteen studies from seven countries were included. Across studies, average DUED weighted by sample size was 29.9 months for anorexia nervosa, 53.0 months for bulimia nervosa and 67.4 months for binge eating disorder. A younger age at time of first treatment was indicative of shorter DUED. Retrospective studies suggest that a shorter DUED may be related to a greater likelihood of remission. Manipulation of DUED by shortening service‐related delays may improve clinical outcomes. Conclusions: Data on length of DUED provide a benchmark for early intervention in EDs. Preliminary evidence suggests DUED may be a modifiable factor influencing outcomes in EDs. To accurately determine the role of DUED, definition and measurement must be uniformly operationalised. Highlights This systematic review is the first to examine duration of untreated eating disorder (DUED) across different eating disorders. Definitions and measurement of DUED and its components vary considerably between studies. Across different eating disorders average DUED weighted by sample size ranges from approximately two and a half years (for anorexia nervosa) to nearly 6 years (for binge eating disorder). DUED appears to be related to age such that younger patients have shorter DUED.